2015
DOI: 10.1155/2015/405234
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Endothelin System in the Vascular Dysregulation Involved in Retinitis Pigmentosa

Abstract: Retinitis pigmentosa is a clinical and genetic group of inherited retinal disorders characterized by alterations of photoreceptors and retinal pigment epithelium leading to a progressive concentric visual field restriction, which may bring about severe central vision impairment. Haemodynamic studies in patients with retinitis pigmentosa have demonstrated ocular blood flow abnormalities both in retina-choroidal and in retroocular vascular system. Moreover, several investigations have studied the augmentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…OBF in RP patients is reduced, obviously secondary to the degeneration of the retina. However, an additional primary component of OBF reduction is likely [18,19] as OBF reduction precede a major degeneration [6,10,13], and blood flow is reduced also in the retroocular vessels [6] and even in cutaneous capillaries [6] and ET in the circulating blood is increased. What could be the cause of this primary component?…”
Section: Increased Prevalence Of Flammer Syndrome In Patients With Rementioning
confidence: 99%
“…OBF in RP patients is reduced, obviously secondary to the degeneration of the retina. However, an additional primary component of OBF reduction is likely [18,19] as OBF reduction precede a major degeneration [6,10,13], and blood flow is reduced also in the retroocular vessels [6] and even in cutaneous capillaries [6] and ET in the circulating blood is increased. What could be the cause of this primary component?…”
Section: Increased Prevalence Of Flammer Syndrome In Patients With Rementioning
confidence: 99%
“…It has been shown that many pathogenic stimuli such as diabetes and oxidative stress induce vascular dysfunction, leading to atherosclerosis, ischemia, inflammation and thrombosis may alter the regulation of retinal and choroidal blood flow [10]. According to recent studies, alteration in SFCT might be related with microvascular dysregulation entities [11][12][13][14]. OCT is a noninvasive and rapid method for multi-modal imaging the retina and choroid.…”
Section: Introductionmentioning
confidence: 99%
“…For retinal vascular changes, studies suggest that a reduced retinal blood flow could be a response to a decreased metabolism after ganglion cell death and a loss of photoreceptors due to reactive vessel constriction [21-23]. This hypothesis has been supported by the finding of an increase in endothelin-1, a powerful endogenous vasoconstrictor factor in the eyes of retinitis pigmentosa patients [22, 24, 25]. In our study, the postvitelliform group of BVMD revealed a reduction in superficial vessel density compared to the vitelliform group, although the difference did not reach a significant level, possibly due to the limited sample size.…”
Section: Discussionmentioning
confidence: 99%